Local Community Empowerment in the Special Autonomy Law in Papua Province - Usman Pakasi (Department of Government Affairs and Administration, Universitas Muhammadiyah Yogyakarta, 2012)
The establishment of the 2001 Special Autonomy Law in Papua Province is not exempted from economic, political and socio-cultural problems. The law is intended to empower the people by preserving their interests and upholding the basic rights of native Papuans. This research aims at finding out a theoretical understanding on the forms of local community empowerment during the implementation of special autonomy in Papua Province. The study is performed through a qualitative approach with a phenomenological strategy. The research was conducted at a location in Jayapura. Empirical data were obtained using the techniques of observation, in-depth interviews, and other secondary data. The implementation of Special Autonomy in Papua Province has brought forth a fundamental change in the approaches and policies of community development, particularly local community empowerment that includes indigenous communities, women, and religion. Local community empowerment in the economic and socio-cultural aspects represents the effort to improve the welfare and sense of justice within the local community in development.